2021
DOI: 10.2323/jgam.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of cellulase-producing <i>Microbulbifer</i> sp. from marine teleost blackfish (<i>Girella melanichthys</i>) intestine and the enzyme characterization

Abstract: Isolation of cellulase-producing Microbulbifer sp. from marine teleost blackfish (Girella melanichthys) intestine and the enzyme characterization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A Microbulbifer sp. strain was recently isolated from the intestine of the herbivorous teleost Girella melanichthys and was found to degrade cellulose [ 70 ], a rather useful trait for the omnivorous D. vulgaris midgut in the current study. Thaumasiovibrio is a recently described genus [ 71 ] and has not yet been reported to be associated with fish.…”
Section: Discussionmentioning
confidence: 99%
“…A Microbulbifer sp. strain was recently isolated from the intestine of the herbivorous teleost Girella melanichthys and was found to degrade cellulose [ 70 ], a rather useful trait for the omnivorous D. vulgaris midgut in the current study. Thaumasiovibrio is a recently described genus [ 71 ] and has not yet been reported to be associated with fish.…”
Section: Discussionmentioning
confidence: 99%
“…A Microbulbifer sp. strain was recently isolated from the intestine of the herbivorous teleost Girella melanichthys and was found to degrade cellulose [Tanaka et al 2021], a rather useful trait for the omnivorous D. vulgaris midgut in the current study. Thaumasiovibrio is a recently described genus [Amin et al 2017] and has not yet been reported to be associated with fish.…”
Section: Discussionmentioning
confidence: 99%
“…Microbulbifer sp. Strain GL-2, the bacterium used in the present study, was isolated from the intestine of a blackfish (Girella melanichthys) (Tanaka et al, 2021). The whole-genome sequence of this strain has been deposited in DDBJ/EMBL/GenBank as Accession Number AP019807 (Sugimoto et al, 2020); a circular map of the genome is shown in Fig.…”
Section: Bacterial Strains and Culturementioning
confidence: 99%
“…In previous work, we isolated Microbulbifer sp. Strain GL-2 from the intestine of blackfish (Girella melanichthys), an omnivorous marine teleost, and reported that this bacterium exhibits high levels of cellulase activity (Tanaka et al, 2021). Species of the genus Microbulbifer, proposed by González et al (1997), have been isolated from marine sediments (Zhang et al, 2011), deep-sea sediments (Miyazaki et al, 2008), and seaweeds (Nishijima et al, 2009).…”
Section: Introductionmentioning
confidence: 99%